Sosialisasi Nilai-Nilai Pendidikan Karakter Bangsa Siswa di Sekolah Menengah Atas Negeri 19 Palembang - Dahlia Zairina Dahlia; Ridhah Taqwa Ridhah; Mulyanto Mulyanto (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
This research aims to analyse the ways in sosializing values of national character building for the students. The study described the ways of the teachers of senior high school 19 in sosializing the values of national character building. The research used qualitative method and the data collected by primary and second data. The analysis of data used by descriptive technique, interviewing conducted with the teachers of each subjects. Observing carried out in the clases when the teachers were teaching. From this research, it could conclude that the ways of teacher to socialize the values of national character building in teaching and learning were presenting repeatly, discussing, giving tasks, giving examples, and doing habit. Of course, in sosializing the values of national character building, the teachers faced any bars, but finally, they could solved the bars by doing cooperating among the teachers in the school.Â